(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Electrical and electronic equipements are classified as devices that operate on electrical current and electromagnetic fields. These EEE are transformed into WEEE after reaching the end of their useful lives. The usage of electrical and electronic equipment has expanded quickly, and because of their shorter lifespans, a lot of e waste is produced globally. WEEE production reached 44.7 Mt in 2016 and would reach 52.2 Mt by 2021. The amount of elements in e-waste, including lead, chromium, arsenic, cadmium, and others, makes it dangerous for both the environment and living things. Only the estimation of mobile phones and personal computers at the University of Kashmir in J&K is the focus of this study. For that reason, I anticipate e-waste creation using a modified exponential equation and utilized the end-of-life model as a basis model to estimate current e-waste generation. At the University of Kashmir, a questionnaire survey was undertaken to learn how consumers dispose of their electronic devices once they have served their purpose. The typical life lengths of electronic devices (such as mobile phones and personal computers) have upper and lower bounds in two scenarios, respectively. The study’s findings indicated that, in the case of mobile phones, the total amount of garbage created for 2021 will be close to 313.88 units and might reach as high as 561.57 units by 2025. The total amount of garbage produced under the lower limit is projected to be 358.15 units in 2021 and to rise to 599.05 units by 2025. Similar to PCs, the total waste created by PCs will increase up to 551.08 units by 2025, from 298.52 units in 2021. The total amount of garbage produced under a reduced restriction, however, was 325.72 units in 2021 and will rise to 581.84 units by 2025. As a result, enough infrastructures should be in place to handle the volume of trash that is produced, and this assessment can serve as a basis for politicians to express timely concern and take appropriate action to route e-waste from its user to disposal.